Comparative study of maternal and perinatal outcomes between elective and emergency caesarean section in term pregnancy at a tertiary care centre - Vishwambharrao Warwantkar, Prachi; Jacob, Shyla; Gupta, Himani; Bute, Anita Suresh; Shrikrishna Dhekale, Dipali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: One of the most common surgical procedures done worldwide is the Caesarean section. The goal of the current study is to ascertain the problems and outcomes for mothers and newborns in two groups of pregnant women who had elective and emergency caesarean sections. So that measures can be taken to reduce morbidity and mortality in near future. Methods: A prospective comparative observational study carried out in department of Obstetrics and Gynecology, Jawaharlal Nehru Hospital and Research Centre, Bhilai, Chhattisgarh. All patients who underwent caesarean section are divided into two groups elective and emergency. Two groups were compared on the basis of different parameters like age, parity, booking status, indication, maternal and neonatal complications. Results: The incidence of caesarean section was 51.15%. The proportion of elective and emergency CS was 39.55% and 60.44% respectively. Most of the complications were more common in emergency group. Conclusions: The incidence of caesarean section is high in JLNH&RC, Bhilai and overall complication rate was more common in emergency group.